Requirements for the Training of Masters of Natural Sciences of Pedagogical Higher Educational Institutions - Hladun, T. (Journal of Education, Health and Sport, 2019)
The article deals with the issues of training future teachers of natural sciences; findings: what requirements for professional education are typical for the training of a teacher of a new formation; what role in the professional development of specialists of pedagogical HEI has professional training and what shortcomings in the training of masters of natural sciences occur at the present stage of development of higher education; areas of modernization of vocational education and physical education, in particular, are identified by scientists.